Characters and their affiliations in the novel The Thirteenth Month by Ahmed Saadawi an exploratory study derived from a master`s thesis - Mohammed, Bestun Jamal Mohammed; Prof.Dr, Hazha Abas Ali Ali (Sulaimani Journal for Humanities, 2025)
This study aims to highlight the affiliation of the characters in Ahmed Saadawi's novel "The Thirteenth Month." This study employs a set of mechanisms that reveal affiliation, whether overt or covert, and uses a narrative approach that explores the characters' inner selves and their feelings, emotions, and reactions toward the revolution and the revolutionaries on the one hand, and toward the ruling authority and its supporters on the other. The novel belongs to post-change narratives that touched upon Iraqi reality due to narrative transformations present in the form and content of the narrative. Its events resemble a series of visual scenes from the October Revolution, declared by revolutionaries and patriots in Baghdad.